Acute responses to on-court repeated-sprint training performed with blood flow restriction versus systemic hypoxia in elite badminton athletes - Valenzuela, P. L.; Sánchez-Martínez, G.; Torrontegi, E.; Vázquez-Carrión, J.; González, M.; Montalvo, Z.; Millet, G. P. (International Journal of Sports Physiology and Performance, 2019)
Purpose: Repeated-sprint training (RS) is commonly conducted in normoxia, but its completion with localized (blood-flow restriction [BFR]) or systemic hypoxia has been proven effective for performance enhancement. Yet, few studies have applied these types of RS sessions in racket sports. The authors aimed to determine the acute responses to these types of training in elite badminton players. Methods: Eight male elite badminton players participated in this randomized crossover study. They performed 3 on-court RS sessions, each consisting of 3 sets of 10 repetitions of 10-s badminton-specific movements in normoxia (RSN), systemic normobaric hypoxia (RSH, FiO2 = 14%), or with BFR (RS-BFR, 40% arterial occlusion pressure). Performance, perceptual (ie, rating of perceived exertion), and physiological (ie, pulse saturation, muscle oxygenation, blood lactate, creatine kinase, heart-rate variability) responses were measured after each set and up to 48 h postsession. Results: RS-BFR induced a greater performance impairment (lower distance and accelerations) and a higher local perceived exertion in the legs than RSN and RSH (P < .05), whereas greater overall fatigue was reported with RSH (P < .05). RSH induced a lower saturation (P < .001), but no differences were observed in muscle oxygenation between conditions. No differences in creatine kinase or heart-rate variability were observed at any time point (from baseline up to 48 h after the session). Conclusions: RS-BFR-and, to a lower extent, RSH-resulted in impaired performance and a higher perceived strain than RSN. However, these 2 hypoxic methods do not seem to induce a long-lasting (post 24-48 h) physiological stress in elite badminton players.